Money Laundering Crimes Arising from The Illegal Trade of Protected Wildlife - Thahir, Irfan Farid; Sunarmi, Sunarmi; Mulyadi, Mahmud; Ekaputra, Mohammad (Locus: Jurnal Konsep Ilmu Hukum, 2024)
Illegal trade in protected wildlife is a criminal offense regulated under Law No. 5 of 1990 on the Conservation of Natural Resources and Ecosystems. The high consumer demand for protected wildlife drives criminals to continue engaging in illegal trade for profit. However, the penalties under this law are considered inadequate and have not been updated since 1990. This study proposes that the crime of trading protected wildlife be classified as a predicate offense for money laundering to impose heavier penalties on perpetrators. By utilizing Law No. 8 of 2010 on Money Laundering, it is hoped that offenders can be subjected to more severe penalties and stronger evidence through tracking the financial flows from illegal trade. This research is normative and descriptive-analytical, and it recommends updating Law No. 5 of 1990 to align with current developments and enhance the deterrent effect against wildlife crime.